Eosinophils Suppress the Migration of T Cells Into the Brain of Plasmodium berghei-Infected Ifnar1-/- Mice and Protect Them From Experimental Cerebral Malaria - Scheunemann, Johanna F.; Reichwald, Julia J.; Korir, Patricia Jebett; Kuehlwein, Janina M.; Jenster, Lea-Marie; Hammerschmidt-Kamper, Christiane; Lewis, Matthew D.; Klocke, Katrin; Borsche, Max; Schwendt, Kim E.; Soun, Camille; Thiebes, Stephanie; et al. (Frontiers in Immunology, 2021)
Cerebral malaria is a potentially lethal disease, which is caused by excessive inflammatory responses to Plasmodium parasites. Here we use a newly developed transgenic Plasmodium berghei ANKA (PbAAma1OVA) parasite that can be used to study parasite-specific T cell responses. Our present study demonstrates that Ifnar1-/- mice, which lack type I interferon receptor-dependent signaling, are protected from experimental cerebral malaria (ECM) when infected with this novel parasite. Although CD8+ T cells responses generated in the spleen are essential for the development of ECM, we measured comparable parasite-specific cytotoxic T cell responses in ECM-protected Ifnar1-/- mice and wild type mice suffering from ECM. Importantly, CD8+ T cells were increased in the spleens of ECM-protected Ifnar1-/- mice and the blood-brain-barrier remained intact. This was associated with elevated splenic levels of CCL5, a T cell and eosinophil chemotactic chemokine, which was mainly produced by eosinophils, and an increase in eosinophil numbers. Depletion of eosinophils enhanced CD8+ T cell infiltration into the brain and increased ECM induction in PbAAma1OVA-infected Ifnar1-/- mice. However, eosinophil-depletion did not reduce the CD8+ T cell population in the spleen or reduce splenic CCL5 concentrations. Our study demonstrates that eosinophils impact- CD8+ T cell migration and proliferation during PbAAma1OVA-infection in Ifnar1-/- mice and thereby are contributing to the protection from ECM.